1981
DOI: 10.2105/ajph.71.12.1329
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' use of mental health services in a comprehensive treatment facility: age, sex and mode of entry.

Abstract: Data are presented from the clinical records of 185 adolescents who were admitted to the mental health service of a youth health center serving a community of military dependents. Eight and onehalf per cent of the population made a first visit to the center during an eight month period. Midadolescence (age 15-16) was the age period when patients began to refer themselves to mental health services in significant numbers. The importance of parents as referral

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
(2 reference statements)
1
6
1
Order By: Relevance
“…In an extensive review of the National Institute of Mental Health psychiatric case register (Rosen, Bahn, Shellow, & Bower, 1965), 14-15-year-olds were found to have the highest clinic utilization rates. Other studies have also found mid-adolescence (ages 14-17) to be highly related to service use (Mitchell & Smith, 1981; Roughmann, Babigian, Goldberg, & Zastowny, 1982). Mitchell and Smith examined the records of 185 adolescents referred to the mental health service of a youth health care center and found an increase in self-referrals between the ages of 15 and 16.…”
Section: Literature Reviewmentioning
confidence: 86%
See 2 more Smart Citations
“…In an extensive review of the National Institute of Mental Health psychiatric case register (Rosen, Bahn, Shellow, & Bower, 1965), 14-15-year-olds were found to have the highest clinic utilization rates. Other studies have also found mid-adolescence (ages 14-17) to be highly related to service use (Mitchell & Smith, 1981; Roughmann, Babigian, Goldberg, & Zastowny, 1982). Mitchell and Smith examined the records of 185 adolescents referred to the mental health service of a youth health care center and found an increase in self-referrals between the ages of 15 and 16.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Two of the variables in Table 1—poor school performance and maternal level of education—were not studied directly but only alluded to. Studies have reported that a high proportion of children were referred by the school system and that the referred children were experiencing school difficulties (Garralda & Bailey, 1988; Mitchell & Smith, 1981; Rosen et al, 1965; Wolff, 1967). Some studies have reported that maternal level of education may be related to use of mental health services.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Family contextual factors also influence this process. Some ofthese factors have been identified in available studies and include higher levels of maternal education (23)(24)(25); low family income (23,(26)(27)(28); parental psychiatric problems (23,27,(29)(30)(31); and family dysfunction and/or adversity (32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Proponents of the social network perspective might argue that children are connected to services through an interconnected web of informal and formal helpers, caretakers, or significant others of which each of them have their own gender biased lens (Lott et al 1999;Michell and Smith 1981). Central 'helpers' in children's social networks include informal network members, such as family and friends, or more formal network members, such as school personnel, human service providers, law enforcement, court and other juvenile justice personnel (Lott et al 1999;Michell and Smith 1981;Settertobulte and Kolip 1997;Zwaanswijk et al 2007). According to this perspective, informal network members are a critical and sequential set of interconnected relationships to children's receipt of services (Pescolido and Levy 2002).…”
Section: Introductionmentioning
confidence: 99%